Analisis Perbandingan Sistem Pendaftaran Tanah di Indonesia, Malaysia, Belanda, dan Australia - Davina Crysanti Aryuhanna; Dwivania Naila Hanifah; Lidya Zahrania Badahda; Aprila Niravita; Muhammad Adymas Hikal Fikri (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study offers an in-depth comparative assessment of land registration systems in Indonesia, Malaysia, the Netherlands, and Australia, acknowledging that variations in historical evolution, legal infrastructures, and administrative mechanisms have shaped each country’s approach to land governance. These foundational distinctions play a crucial role in determining how effectively each nation provides legal certainty, secures land ownership rights, and administers land records with accuracy and efficiency. The analysis explores how differing registration models—ranging from deeds-based to title-based systems—impact levels of transparency, reliability, and public trust in land management institutions. Furthermore, the study identifies the strengths, limitations, and operational challenges within each framework, demonstrating that no single system is universally superior. Instead, the effectiveness of land registration practices depends on how well they align with the socio-legal context, institutional capacity, and administrative heritage of each region. The findings emphasize the importance of context-specific policy formulation, suggesting that land administration reforms should not merely replicate foreign models but must be adapted to local legal traditions and governance needs. Overall, this research underscores the necessity of designing land registration systems that enhance legal protection, promote efficient land administration, and strengthen the long-term security of landowners’ rights across diverse jurisdictions.